Gardening with Annuals in Florida - Sydney Park Brown (EDIS)
Annuals offer an almost infinite variety of flower color and plant form. They brighten landscape beds and add a splash of color to a porch, deck, or patio when placed in containers. Some also make good cut flowers. This revised 8-page fact sheet covers selection and use, site preparation and planting, care, and cultural practices. Written by Sydney Park Brown, and published by the UF Department of Environmental Horticulture, September 2011.